Extending battery life and reducing charging costs in electric vehicles through converter selection for on-board chargers - Jangam Kishore Babu; Ganney Poorna Chandra Rao; Puvvula Venkata Rama Krishna; Swathi Karike; Sailaja Kethireddy; Sareddy Venkata Rami Reddy; B. Nagi Reddy; Rekha Rangam (Institute of Advanced Engineering and Science, 2026)
The electric vehicle (EV) sector is among the quickly expanding industries today. Global commitment to reducing pollution levels promotes interest in EVs. Fuel combustion engines emit around 10% of the globe's greenhouse gas emissions, which exacerbate the greenhouse effect. The emissions from electric vehicles are 17–27% less than those from internal combustion engines. The short battery life, high cost of charging, and lack of charging stations are some disadvantages of electric vehicles. The goal of this study is to suggest the ideal converter for the on-board charger (OBC), one that can extend battery life by lowering charging current at extremes of state of charge (SOC) and lower charging costs by increasing power factor (PF). The current control range than the isolated converter using transformers. Lastly, an analysis of the MATLAB/Simulink output findings is conducted to verify the effectiveness of the suggested OBC design with a non-isolated converter.